Online optimisation and active control of the cure process of thick composite laminates - Tifkitsis, Konstantinos; Winistoerfer, A.; Skordos, Alexandros A. (Elsevier, 2023)
This paper addresses the development of an active control tool for the in-situ optimisation of the cure process of thick composite parts. The methodology integrates a cure process model with real time monitoring data exploring potential temperature dwells that accelerate the curing while avoiding undesirable thermal gradients. The cure process simulation is based on a Finite Element (FE) model solution validated in the curing of a thick composite flat panel with an average absolute error of about 1.8 °C. The active control tool interacts PID controller of an oven setting a new cure temperature periodically. The implementation of active control tool during the curing of a thick carbon fibre/epoxy cable has the capability to determine in real time optimal solutions minimising process duration whilst also satisfying constraints in temperature overshoot. A process duration reduction of about 70 % can be achieved compared to a nominal cure cycle with a maximum temperature overshoot lower than 9 °C. The active control tool can replace off-line optimisation tools exploiting in situ with real time monitoring to drive the process and minimise the effects of uncertainty.
Keywords: Composites; Process monitoring; Cure; Automation; Process optimisation